2016
DOI: 10.1016/j.carbon.2016.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Strong and machinable carbon aerogel monoliths with low thermal conductivity prepared via ambient pressure drying

Abstract: Carbon aerogels are among the most attractive porous carbon materials currently, but their real-world applications are greatly limited by their high cost, complicated preparation process and low mechanical properties. Herein, we report a very facile route to prepare lightweight but mechanically strong carbon aerogel monoliths (CAMs), through a sol-gel polymerization of linear phenolic resin and hexamethylenetetramine (HMTA), followed by ambient pressure drying and carbonization. The good capability of linear p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(60 citation statements)
references
References 46 publications
1
59
0
Order By: Relevance
“…As a result, solid conductivity is considered as a main heat transfer mechanism. Solid conductivity is governed by the density of aerogels . The presence of crosslinking agents increases the neck size and enhanced the connection of the secondary particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, solid conductivity is considered as a main heat transfer mechanism. Solid conductivity is governed by the density of aerogels . The presence of crosslinking agents increases the neck size and enhanced the connection of the secondary particles.…”
Section: Resultsmentioning
confidence: 99%
“…Although some of those monoliths had greatly decreased surface areas, changing the solvent used to produce the gels from methanol to ethanol increased the surface area in one instance from 6 to 220 m 2 g −1 with little influence on the modulus, elastic recovery, porosity, and density. Jia et al . reported a new route to prepare a lightweight carbon aerogel with high mechanical strength as a thermal insulator.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon aerogels, the 3D porous network structure formed by carbon nanomaterials, have received widespread attention since they were firstly obtained, due to their fascinating physical properties, including low apparent density, large specific surface area, abundant pore structure, high electrical conductivity, good chemical stability, and environmental compatibility. Based on the above characteristics, a kaleidoscope of carbon aerogels has been fabricated and used widely in energy storage,, thermal insulation, environmental clean‐up,, chemical sensors,, and biomedical and pharmaceutical applications , . As shown in Figure , the number of publications concerning carbon aerogel have been increasing in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…[3,[5][6][7][8][9][10] The tribo-tunneling transport tip-enhanced current generation, as reported by Liu et al [3,6] using conductive-atomic force microscope (C-AFM), show that the tribo-tunneling current density ( J) output can be boosted by the nano-sized contact (tip radius R ≈ 30 nm) up to 10 6 A m −2 due to the enhanced electronic excitation and strong localized electric field E. It has been reported that a micro-tip (tip radius R ≈ 30 µm) sliding system produces a current density of 35 A m −2 while larger tip radius (R ≈ 100-300 µm) yields a current density of 10 A m −2 in the test probe sliding system. [11] It has been widely used for nanocomposite, electrodes, desalination filters, and heterogeneous catalysis due to its large surface area. The metal micro-tips also cause substrate surface scratching, which impacts the sustainability of the power generation.…”
mentioning
confidence: 99%
“…[11] It has been widely used for nanocomposite, electrodes, desalination filters, and heterogeneous catalysis due to its large surface area. [11] It has been widely used for nanocomposite, electrodes, desalination filters, and heterogeneous catalysis due to its large surface area.…”
mentioning
confidence: 99%